2022
DOI: 10.2991/assehr.k.220301.128
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Ulap Doyo Handheld Handbag for Application in Pokant Takaq Small and Medium Enterprise, Kalimantan Timur to Support Tourism Sector

Abstract: Typical East Kalimantan Handicraft is one of the fields that has a major contribution to improving the regional economy. Craft is one of the creative industry sectors, and creative industries in Indonesia contribute an average of 6.3 percent of GDP to the total National GDP with a value of Rp. 104.6 trillion in 2002-2006. However, not much product development has been carried out by UKM Crafts in East Kalimantan. There has been no attempt to develop products based on customer preferences for handicraft product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…In Eastern Kalimantan, C. latifolia fibers have traditionally been used for weaving fabrics and handbags. 31,32 Additionally, the plant was considered for its potential as a natural dye, and Shaari 30 found that the leaves and flowers produced promising colors ranging from dark green to yellow, which can act as dyes.…”
Section: Introductionmentioning
confidence: 99%
“…In Eastern Kalimantan, C. latifolia fibers have traditionally been used for weaving fabrics and handbags. 31,32 Additionally, the plant was considered for its potential as a natural dye, and Shaari 30 found that the leaves and flowers produced promising colors ranging from dark green to yellow, which can act as dyes.…”
Section: Introductionmentioning
confidence: 99%